Data mining as a tool in Personalized web sites (Journal of the College of Basic Education, 2022)
this paper studies the problem of putting data mining techniques in personalized web services as assistance tool for collaborative filtering tool of personalization. Collaborative filtering collect information for the customer from the opinion of other people in some fields, by matching the favorites of customer with others like, matching the same data and meta data, here in this article will consider the algorithm of A-prior from association rule method of data Mining as assistance tool to get collaborative filtering from the customer baskets to find out the associate things normally other customers likes to buy within their baskets.